The risks from state and local government employee pension plans: A stochastic simulation analysis - Mark J. Warshawsky (American Enterprise Institute (AEI), 2024)
There is a large professional literature on the correct measurement of the funded status of and indicated employer contributions to government employee pension plans. But static measures do not provide a quantification of the risk that plans could represent in the future in various possible investment environments. This is better done through stochastic simulation projections. Using a 2022 data base of 187 large pension plans, basic plan features and conditions, actuarial relationships, simple economic projections, and varied bond and stock investment returns based on past ten-year historical periods in the US and the current asset allocation of the plans, I create a risk model. This risk assessment is denominated as the range of reasonably possible future actuarial funded ratios and amounts of indicated employer contributions across plans, when investment performance is poor but within historical experience. Several plans would be at or near insolvency, about 11 percent of plans would see very large drops in funded status, while employer contributions would, on average, double, and for about one in seven plans, triple.
Keywords: G17; G23; H75; J32; 330; Public pension plans; funding; costs; investment risk; stochastic projections